Pengaruh Kualitas Produk dan Gaya Hidup terhadap Keputusan Pembelian Iphone dengan Personal Branding sebagai Variabel Moderat Mahasiswa Universitas Terbuka Surabaya - Arina Larasati Amalia; Agung Pujianto; Ute Chairuz M. Nasution (Politeknik Kampar, 2025)
Everything must continue to progress with the times, including product quality and lifestyle. Although it looks simple, product quality must continue to be developed to suit lifestyles in order to attract buyers, especially in purchasing iPhones among students at Universitas Terbuka Surabaya. The phenomenon of increasing iPhone use among UT students shows that there is encouragement from aspects of product quality, digital lifestyle, and the need to build self-image through personal branding. This study includes quantitative research using the Google form filling method. The analysis technique used is Moderated Regression Analysis (MRA). The results of the study indicate that product quality and lifestyle have a significant influence on iPhone purchasing decisions. In addition, personal branding is proven to moderate the influence of product quality and lifestyle on purchasing decisions. These findings indicate that UT students not only consider the features and design of the iPhone, but also make it part of their identity that supports their professional image in academic and work environments.